Schistosoma mansoni: on the possibility of Indian buffalo (Bubalus bubalis) being experimentally infected - Paulo Marcos Zech Coelho; Walter S. Lima; Raimundo H. G. Nogueira (Revista da Sociedade Brasileira de Medicina Tropical, 1989)
Male Indian buffalo (Bubalus bubalis) calves were submitted to Schistosoma mansoni infection by percutaneous, oral and subcutaneous routes. No worms or eggs were found in four of the animals tested. Bubalus bubalis appears to be refractory for S. mansoni.